More Than Wargaming: Exploring the Miniaturing Pastime - Mikko Meriläinen; Jaakko Stenros; Katriina Heljakka (United States, 2022)
Background. Miniaturing, or painting, collecting, and gaming with miniature wargaming figurines, is a popular, yet vastly underresearched subject. Previous research suggests a multitude of practices and ways of engaging with miniatures.
Aim. This qualitative study explores the various elements of miniaturing to both map the phenomenon and build a foundation for further research.
Method. Miniaturing is explored through a thematic analysis of 127 open-ended survey responses by adult Finnish miniature enthusiasts.
Results. Responses suggest a dual core to miniaturing, consisting of crafting and gaming. In addition to these core activities, storytelling, collecting, socializing and displaying and appreciating appear commonly, with considerable individual variation. The different elements are closely intertwined, based on individual preferences and resources.
Discussion. As a pastime, miniaturing occupies an interesting position with elements of crafting, toy play and gaming, and escapes easy situating. The considerable individual variation in enthusiasts’ preferences suggests a multitude of fruitful approaches in further research.